National service in Singapore : rewarding the positive - minded - Chan, Samuel (2011)
A kaleidoscope of benefits has been initiated to reward National Servicemen. There are, however, those for whom monetary compensation pales in comparison to the reward of service fulfilment. Harnessing such positive